Pengembangan Bahan Ajar Menulis Deskripsi Menggunakan Model Kooperatif Round Table dengan Media Audio pada Siswa Kelas X SMA - Siti Halijah; Susilo Susilo; Widyatmike Gede Mulawarman (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
The purpose of this study is to produce teaching materials that can enhance the creativity of the learning process, increase development and improve the quality of the application of the development of cooperative models of the type of Round Table with audio media in improving the learning outcomes of writing the description of class X high school students. This research is a research development or Research & Development (R&D). Research and Development is a research method used to produce certain products and test the effectiveness of these products. The results of the study can be concluded from the analysis of teaching material scores by material expert teachers and media expert teachers obtained an average score of 4.74 or 94.74% of the maximum average score of 5.00 with a very good collection. The application of the development of teaching materials in the excellent category is 29 or 90.62% of the students' attention to the material delivered and student activity is included in the excellent category of 30 or 93.75% of students. The quality of the application of the development of cooperative learning model teaching materials of the round table type in learning 100% with very good assessment and the results of post-test analysis of 96.87% indicate whether the learning tools used have practical qualities and the learning devices developed have effective qualities according with student completeness of more than 75%.